Environmental DNA (eDNA) From the Wake of the Whales: Droplet Digital PCR for Detection and Species Identification - Baker, C. Scott; Steel, Debbie; Nieukirk, Sharon; Klinck, Holger (Frontiers in Marine Science, 2018)
Genetic sampling for identification of species, subspecies or stock of whales, dolphins and porpoises at sea remains challenging. Most samples have been collected with some form of a biopsy dart requiring a close approach of a vessel while the individual is at the surface. Here we have adopted droplet digital (dd)PCR technology for detection and species identification of cetaceans using environmental (e)DNA collected from seawater. We conducted a series of eDNA sampling experiments during 25 encounters with killer whales, Orcinus orca, in Puget Sound (the Salish Sea). The regular habits of killer whales in these inshore waters allowed us to locate pods and collect seawater, at an initial distance of 200 m and at 15-minute intervals, for up to two hours after the passage of the whales. To optimize detection, we designed a set of oligonucleotide primers and probes to target short fragments of the mitochondrial (mt)DNA control region, with a focus on identification of known killer whale ecotypes. We confirmed the potential to detect eDNA in the wake of the whales for up to two hours, despite movement of the water mass by several kilometers due to tidal currents. Re-amplification and sequencing of the eDNA barcode confirmed that the ddPCR detection included the ‘southern resident community’ of killer whales, consistent with the calls from hydrophone recordings and visual observations.